Localized dynamics of thin-walled shells - Mikhasev, G. I. (Gennadiĭ Ivanovich); Tovstik, P. E. (Boca Raton, FL : Chapman and Hall/CRC, 2020)
Localized Dynamics of Thin-Walled Shells focuses on localized vibrations and waves in thin-walled structures with variable geometrical and physical characteristics. It emphasizes novel asymptotic methods for solving boundary-value problems for dynamic equations in the shell theory, in the form of functions which are highly localized near both fixed and moving lines/points on the shell surface. Features First-of-its-kind work, synthesizing knowledge of the localization of vibrations and waves in thin-walled shells with a mathematical tool to study them Suitable for researchers working on the dynamics of thin shells and also as supplementary reading for undergraduates studying asymptotic methods Offers detailed analysis of wave processes in shells with varying geometric and physical parameters
Chapter 1: Introduction. Chapter 2: Equations of the two-dimensional theory of shells. Chapter 3: Localized vibration modes of plates and shells of revolution. Chapter4: Localized vibration modes of cylindrical and conic shells. Chapter5: Localized Parametric Vibrations of Thin Shells. Chapter6: Wave Packets in Medium-length Cylindrical Shells. Chapter 7: Effect of External Forces on Wave Packets in Zero Curvature Shells. Chapter 8: Wave Packets in Long Shells of Revolution Travelling in the Axial Direction. Chapter 9: Two-dimensionalWave Packets in Shells of Arbitrary Shape.
OCLC-licensed vendor bibliographic record.
Keywords: Thin-walled structures